Implementation of the Single Data Population Policy at the Central Bureau of Statistics and the Directorate General of Population and Civil Registration of the Ministry of Home Affairs - Abdul Azis, Mohamad; Rahayu, Neneng; Widjayanti, Arifiani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2024)
There is an overlap in policies between Statistics Law No. 16 of 1997 and Law No. 24 of 2013. The difference in data from the Central Statistics Agency and Dukcapil causes confusion for data users. The research aims to determine the factors that influence the effectiveness or ineffectiveness of the content and context of the Implementation of the One Population Data Policy and to develop strategies in order to improve the Implementation of the One Population Data Policy of the Central Bureau of Statistics with Dukcapil. This discussion is about how to implement a single population data policy from the content and context in Merilee S. Grindle's view. The results of the research found that based on the content of policy, the factors that influence the implementation of the one population data policy cause the implementation of the one population data policy of the Central Bureau of Statistics and Dukcapil not to run optimally, this is because there are inhibiting factors that influence the implementation of the one population data policy, namely the interest factor of the target group, the type of benefit factor and the degree of change desired. Based on the Policy Implementation Context (Context of Implementation), there are inhibiting factors that influence the implementation of population data policies, namely the factor of how much power, interest and strategy the actors involved in implementing the policy have. Conclusion: The process of implementing the single population data policy between the Central Statistics Agency and Dukcapil is already underway, but it is not yet running optimally, requiring a long process. To realize one population data, the following recommendations need to be made: Strengthening the device system used to support the implementation of population data integration and technological maintenance. Eliminate sectoral egos between related agencies. to synchronize population data, coordinate continuously and carry out joint monitoring and analysis between agencies.